2013
DOI: 10.3109/14767058.2013.858318
|View full text |Cite
|
Sign up to set email alerts
|

Gestational weight gain in overweight and obese women enrolled in a healthy lifestyle and eating habits program

Abstract: A caloric restriction associated to changes in eating behavior and constant physical activity, is able to reduce gestational weight gain and related pregnancy complications in obese women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
166
2
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(195 citation statements)
references
References 21 publications
4
166
2
4
Order By: Relevance
“…Although not all GDM events can be prevented, lifestyle interventions introduced early in pregnancy or before pregnancy have the potential of preventing GDM development, at least among some women. This is supported by the promising findings from large observational studies on pre-pregnancy diet and lifestyle (Table 1), aforementioned positive findings from studies that started the intervention early in pregnancy [31][32][33][34][35][36][37][38][39][40], and by the successful prevention of type 2 diabetes with diet and lifestyle modification among non-pregnant individuals, for example, in the FDPS [26] and in the US DPP [27]. Finally, findings from animal and human medical studies have demonstrated the biological plausibility of improving insulin sensitivity and secretion through diet and lifestyle modification.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…Although not all GDM events can be prevented, lifestyle interventions introduced early in pregnancy or before pregnancy have the potential of preventing GDM development, at least among some women. This is supported by the promising findings from large observational studies on pre-pregnancy diet and lifestyle (Table 1), aforementioned positive findings from studies that started the intervention early in pregnancy [31][32][33][34][35][36][37][38][39][40], and by the successful prevention of type 2 diabetes with diet and lifestyle modification among non-pregnant individuals, for example, in the FDPS [26] and in the US DPP [27]. Finally, findings from animal and human medical studies have demonstrated the biological plausibility of improving insulin sensitivity and secretion through diet and lifestyle modification.…”
mentioning
confidence: 62%
“…The few studies that did demonstrate a significant beneficial effect of diet and/or physical activity all started the intervention relatively early, in the first trimester, before or near 13 weeks of gestation [31][32][33][34][35][36][37][38][39][40]. For example, among all the published studies to date on physical activity interventions for GDM prevention [41,42], the point estimate for the majority of studies indicate a beneficial effect, yet only those with the intervention starting early in the first trimester had statistically significant findings [33][34][35]38].…”
mentioning
confidence: 99%
“…Of the large number of early lifestyle RCTs, only two, (one HE and one HE&PA intervention) showed a substantial (60-77%) reduction in the proportion of women developing GDM (23,24). Both RCTs were also associated with significant GWG reductions (3.4 kg (in obese participants) and 6.8 kg respectively) that were greater than the average GWG reduction of 1.4 kg that has been achieved in lifestyle RCTs (25).…”
Section: Discussionmentioning
confidence: 96%
“…The dietary intervention, previously used by our research group [10], was introduced to the pregnant women at the first visit in the presence of both a gynecologist and a dietitian and further detailed through a one hour counseling session about the appropriate GWG at term for each BMI category as recommended by IOM [1]. The primary focus of the dietary intervention was decreasing consumption of foods with a high glycemic index and substituting them with healthier alternatives (fresh fruit and vegetables with low glycemic index).…”
Section: Dietary Interventionmentioning
confidence: 99%
“…Indeed, only a few studies have included both diet and PA in their intervention program. In a previous paper, we demonstrated that a multilevel intervention (including caloric restriction, changes in eating behavior, and regular PA from the beginning of pregnancy) in obese women was able to reduce both GWG and related pregnancy complications [10].…”
Section: Introductionmentioning
confidence: 95%